Safety evaluation following immunization of pentavalent vaccine (multi-dose vial): experiences and comparative study - Panda, Bijoy Kumar; Bajaj, Raveena; Surve, Deepika; Deshpande, Ruma (International Journal of Contemporary Pediatrics, 2021)
Background: Combination vaccines have many benefits but sometimes may result in unexpected side effects which may make the vaccine unfit for administration particularly with multidose vials. Methods: Healthy infants aged 6-8 weeks who came for routine immunization of liquid pentavalent vaccine were included in the study. All infants were observed for 30 minutes, post vaccination. Telephonic interview was conducted to detect AEFIs at 1 week and 1 month post vaccination. Results: The common AEFIs were found to be fever and pain at injection site. A comparison of the incidence (per 100 doses) of AEFIs after 1st, 2nd and 3rd dose of pentavalent vaccine showed that AEFIs goes on reducing with dose. Incidence (per 100 doses) of fever and local AEFIs was more (statistically significant) with multi-dose vial pentavalent vaccine. Conclusions: The multi-dose vial liquid pentavalent vaccine was found to be equally tolerable compared to single-dose vial liquid pentavalent vaccine.